Shrinking of the glaciers of East Altai (Shapshal Center) after the maximum of the Little Ice Age - D. A. Ganyushkin; O. S. Konkova; K. V. Chistyakov; D. V. Bantcev; A. V. Terekhov; E. P. Kunaeva; Yu. N. Kurochkin; T. A. Andreeva; D. D. Volkova (Лëд и снег)
Based on the analysis of remote data and field observations, we reconstructed the glaciation of the Shapshal Center (Eastern Altai) for the maximum of the Little Ice Age (LIA) and by the state of the glaciers as of 2001. At the maximum of the LIA, glaciation was represented by 358 glaciers with a total area of 84.43 km2. It was found 87% reduction of the total area of glaciers in the interval from the LIA maximum to 2015. During the reduction, valley glaciers disintegrated and glaciers in the Kargy River basin disappeared. The moraines of the LIA have low lake coverage (0.17% of area), therefore a probability of their breakthrough is low. We obtained data on the retreat of the Mushtuk Glacier (№ 78), the largest one of the Shapshal center, in five time slices from the LIA maximum. The highest retreat rates were reconstructed in the interval 1989–2001, but in the interval 2010–2016 the average rates decreased to 5 m/year. Changes in the mass balance index of the Mushtuk Glacier between from 1961 to 2018 were calculated. A sharp decrease in the mass balance in the 1990s and stabilization of values at a low level after 2001 were found. According to the calculations, the response time of the Mushtuk Glacier was about 9 years. If the current climatic conditions persist, there is reason to assume stabilization of glaciers in the coming years.